2015
DOI: 10.1099/vir.0.000119
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine response in mouse bone marrow derived macrophages after infection with pathogenic and non-pathogenic Rift Valley fever virus

Abstract: Rift Valley fever virus (RVFV) is the most pathogenic member of the genus Phlebovirus within the family Bunyaviridae, and can cause severe disease in humans and livestock. Until recently, limited information has been published on the cellular host response elicited by RVFV, particularly in macrophages and dendritic cells, which play critical roles in stimulating adaptive and innate immune responses to viral infection. In an effort to define the initial response of host immunomodulatory cells to infection, prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
4
10
0
Order By: Relevance
“…Recombinant Zaire Ebola virus expressing eGFP (EBOV-eGFP), and Rift Valley fever virus (strain ZH501; RVFV) were propagated in Vero E6 cells, Far-eastern tick-borne flavivirus (strain Sofjin; RSSEV) was propagated in BHK-S cells, and Crimean-Congo hemorrhagic fever virus (strain IbAr10200; CCHFV) was propagated in SW-13 cells. Virus titers were quantified by plaque assay using respectively Vero E6 (EBOV and RVFV), BHK (RSSEV) or SW-13 (CCHFV) cells, as previously described616263. Titers were reported as log10 pfu/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant Zaire Ebola virus expressing eGFP (EBOV-eGFP), and Rift Valley fever virus (strain ZH501; RVFV) were propagated in Vero E6 cells, Far-eastern tick-borne flavivirus (strain Sofjin; RSSEV) was propagated in BHK-S cells, and Crimean-Congo hemorrhagic fever virus (strain IbAr10200; CCHFV) was propagated in SW-13 cells. Virus titers were quantified by plaque assay using respectively Vero E6 (EBOV and RVFV), BHK (RSSEV) or SW-13 (CCHFV) cells, as previously described616263. Titers were reported as log10 pfu/ml.…”
Section: Methodsmentioning
confidence: 99%
“…RVFV NSs induces cellular damage through various mechanisms including interactions with mitochondria [ 75 ], proteasome [ 76 ], SMAD proteins [ 77 ], nuclear pore protein Nup98 [ 78 ], casein kinase II [ 79 ], p62 involved in general transcription [ 80 ], p53 involved in cell cycle and apoptosis regulation [ 81 ], and ABl2 and the actin cytoskeleton [ 82 ]. In RVFV NSs coding region mutants, virulence is decreased and infection can be characterized by lack of filament formation in nuclei of infected cells [ 83 ], decreased IFN antagonism and inability to degrade PKR [ 84 ], reduced general transcription inhibition and cytotoxicity [ 80 ], and reduced ability to inhibit antiviral signaling by macrophages [ 85 ]. Additionally, human host cell protein STAT3 (signal transducer and activator of transcription 3), a pro-survival protein, specifically targets RVFV NSs to inhibit apoptosis and influence NSs nuclear localization [ 86 ].…”
Section: Family Phenuiviridaementioning
confidence: 99%
“…One study found macrophages and lymphocytes in the brain of a patient that died of encephalitis [9]. The susceptibility of human macrophages to RVF infection and their role during in RVF infection in animal models is fairly well-defined in both in vitro as well as in vivo [26, 27]. Limited studies have focused on the role neutrophil-mediated pathology during RVFV infection compared to macrophages.…”
Section: Discussionmentioning
confidence: 99%